Global capitalism as blood sacrifice: mainstream American comic books and depictions of economic inequality - Phillips, Nickie D. (Critical criminology, 2022)
The past few decades have witnessed unprecedented global economic catastrophes that exacerbated pre-existing socioeconomic inequalities. Although many scholars have attributed the resulting social harms to the failures of neoliberal capitalism - and recognize it as criminogenic - the logics upholding the economic order continue to hold sway among the public. Given that these logics are commonly reinforced through media and popular culture narratives, in this paper we explore how economic inequalities are portrayed in American comic books. We employ a thematic analysis of comic book depictions of mass economic destruction and economic inequality from the financial crisis of 2008 through the Occupy Wall Street movement to the more recent characterization of a post-capitalist existence under the throes of a global plutocracy. In doing so we recognize the potential for re-imagining alternatives to neoliberal capitalism, taking a critical criminological lens to the comic books. We then place The Black Monday Murders, a culmination of portrayals of economic inequality and related violence, in the context of more mainstream comic book depictions and discuss how this particular work exemplifies a rising theme in comics - a purported trade-off between global capitalism and human life, a discussion point that explicitly entered American public discourse during the coronavirus pandemic.